2001
DOI: 10.1097/00001888-200110000-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Incremental Value of Internet-based Instruction as an Adjunct to Classroom Instruction

Abstract: The study documents the incremental value of Internet-based teaching of clinical ethics to sophomore medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 4 publications
0
42
0
2
Order By: Relevance
“…The remaining 42 studies (70%) have been published in the shorter time interval between 2008 and mid 2013 (ie, 5.5 years). Out of all 60 included studies, 33 studies investigated eLearning in the field of medicine [26,28,32,3436,38–41,44,45,49,50,54,5862,6470,72,75,77,78,80,82]. Eleven of the articles [25,27,33,42,43,53,56,74,76,79,83] were exclusively from nursing, 3 [55,57,81] were within the field of physical therapy, whereas 3 other studies within pharmacy [30, 31, 71].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 42 studies (70%) have been published in the shorter time interval between 2008 and mid 2013 (ie, 5.5 years). Out of all 60 included studies, 33 studies investigated eLearning in the field of medicine [26,28,32,3436,38–41,44,45,49,50,54,5862,6470,72,75,77,78,80,82]. Eleven of the articles [25,27,33,42,43,53,56,74,76,79,83] were exclusively from nursing, 3 [55,57,81] were within the field of physical therapy, whereas 3 other studies within pharmacy [30, 31, 71].…”
Section: Resultsmentioning
confidence: 99%
“…Six other studies used open ended [30,33,63,66] or Likert type questionnaires [29] or even “fill in the blank” questions [73]. The rest of the studies measured students’ knowledge gain via other testing means including general numeracy tests [83]; written exams [41, 46, 58, 65]; independent observers’ assessment [79]; cognitive assessment instruments [54]; surgical knowledge test scores [76]; a Diagnostic Thinking Inventory and individual students’ performance in solving clinical reasoning problems [38]; a modified version of the Dartmouth Sleep Knowledge and Attitudes survey [62]; an interactive evaluation about melanoma [26]; an orthodontic examination form for each patient [37]; or some form of a knowledge assessment scale or checklist [42,52,68]. …”
Section: Resultsmentioning
confidence: 99%
“…[16,23] We also found that most students (85.6%) were of the view that IT should be used as a supplement to medical teaching and this was comparable to report of other workers. [14,24] However, less than half of the students (39.5%) want laptop acquisition to be mandatory despite their interest in IT based medical education probably due to the poor financial status of parents and guardians in a poor resource setting and inadequate electrical power which is a prerequisite for operating a laptop. Almost half (49.8%) of the students reported that 50-75% of their lecturers used information technology for teaching and 36.5% reported that their teachers are very efficient in the use of computer in teaching of students.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Similarly, some studies have reported greater student satisfaction with WB approaches, 8,9,11 whereas others have found no difference compared with traditional methods. [13][14][15] Almost uniformly, however, WB learning has been lauded for advantages such as its remote access and interactivity, 16 ability to deliver just-in-time clinical information, 17 and ability to produce equivalent learning outcomes with less study time. 11,12 The importance of teaching medical students to be reproducibly proficient in their clinical skills has been underscored by the addition of the clinical skills component to Step 2 of the United States Medical Licensing Examination, a prerequisite for national licensure in all 50 states.…”
mentioning
confidence: 99%